The influence of social media food marketing on body mass index among college students: public health and media perspectives - Ibrahim, Ali; Bani-Issa, Wegdan; AlMarzouqi, Alounoud; Al-awar, Shamsa; Ibrahim, Samah; Ibrahim, Adam; Ibrahim, Hajar; Khalil, Heba; Abdelrahim, Dana N. (Frontiers in Communication, 2025)
BackgroundSocial media marketing (SMM) has become a powerful tool for influencing food-related decisions among young people. By actively engaging users with targeted, interactive food content, it shapes individual preferences and consumption patterns. This study examines the impact of SMM on obesity development within a sample of college students, highlighting how these marketing strategies may contribute to dietary choices that affect long-term health outcomes.MethodsThis study used a cross-sectional design and recruited students from different colleges in a large university in the UAE. An online survey was conducted to gather participants’ sociodemographic information and included an 18-item questionnaire to explore the influence of SM on students’ food consumption behaviors. Obesity was measured through body mass index (BMI).ResultsIn total, 448 students from different colleges participated in this study; 127 (35%) were male and 291 (65%) were female. The mean BMI was 28.86 ± 5.73 kg/m2 and more than half of the participants (n = 255, 56.9%) were classified as obese. The three most commonly used SM platforms were TikTok (41.1%), Instagram (16.3%), and WhatsApp (11.4%). Most participants (n = 427, 95%) reported that the SM platform impacted their food consumption decisions. Two-thirds (65.8%) believed that food or dishes that received more likes/shares on SM were healthier and 49% followed about and consumed the food or dishes that celebrities/influencers shared on SM. Compared with the non-obese group, obese/overweight participants were more likely to be in their first year of college, reported habitually using SM for daily decision-making, had a screen time of >4 h, and reported that SM impacted their food-related decisions (p ≤ 0.05).ConclusionAwareness campaigns should therefore focus on utilizing SM as a positive marketing tool to promote healthy dietary behaviors, provide accurate nutritional knowledge, and support healthy lifestyle choices in the student/young adult population.